2015
DOI: 10.1016/j.iref.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Volatility spillovers in EMU sovereign bond markets

Abstract: AbstractsWe analyse volatility spillovers in EMU sovereign bond markets. First, we examine the unconditional patterns during the full sample (April 1999-January 2014) using a measure recently proposed by Diebold and Yılmaz (2012). Second, we make use of a dynamic analysis to evaluate net directional volatility spillovers for each of the eleven countries under study, and to determine whether core and peripheral markets present differences. Finally, we apply a panel analysis to empirically investigate the determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 38 publications
5
18
0
Order By: Relevance
“…This research, while providing a significant advance of technique, found its sources in the works of Baillie and Bollerslev (1991) , Susmel and Engle (1994) and Koutmos and Booth (1995) , who had examined multi-frequency and cross-market spillovers in foreign exchange and equity markets respectively. Regional volatility has since been examined in Japan ( Kim and Rhee (1997) ; Ng (2000) ); the United States ( Tse (1999) ); South Korea ( Pyun et al., (2000) ); Hong Kong ( Gannon (2005) ); Europe ( Baele (2005) ; Fernandez-Rodriguez et al., (2015) ); Taiwan ( Lin (2006) ); Canada ( Krause and Tse (2013) ), the United Kingdom ( Antonakakis et al., (2016) ) and in consideration of the BRICs in its entirety ( Bekiros (2014) ; Syriopoulos et al., (2015) ; Mensi et al., (2016) ). Further, Balli et al., (2015) identified significant spillover effects from developed markets to emerging markets.…”
Section: Previous Literaturementioning
confidence: 99%
“…This research, while providing a significant advance of technique, found its sources in the works of Baillie and Bollerslev (1991) , Susmel and Engle (1994) and Koutmos and Booth (1995) , who had examined multi-frequency and cross-market spillovers in foreign exchange and equity markets respectively. Regional volatility has since been examined in Japan ( Kim and Rhee (1997) ; Ng (2000) ); the United States ( Tse (1999) ); South Korea ( Pyun et al., (2000) ); Hong Kong ( Gannon (2005) ); Europe ( Baele (2005) ; Fernandez-Rodriguez et al., (2015) ); Taiwan ( Lin (2006) ); Canada ( Krause and Tse (2013) ), the United Kingdom ( Antonakakis et al., (2016) ) and in consideration of the BRICs in its entirety ( Bekiros (2014) ; Syriopoulos et al., (2015) ; Mensi et al., (2016) ). Further, Balli et al., (2015) identified significant spillover effects from developed markets to emerging markets.…”
Section: Previous Literaturementioning
confidence: 99%
“…Their study concludes that volatility spillover effects and the cross‐correlation have been strenghtened as a result of the common currency (Euro). Similarly, Fernández‐Rodríguez, Gómez‐Puig, and Sosvilla‐Rivero (2015), in a panel data setting, examine the volatility spillovers in European Monetary Union (EMU) sovereign bonds market. Using the original eleven (11) member countries, they find Italy and Spain as the net transmitters of bond yield shocks to other countries, while Portugal and Ireland are established to be the net receivers of the shocks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is in agreement with the findings of World Bank (2009) which comes out to similar outcomes (see World Bank 2009). Fernández-Rodríguez et al (2015) also report the same for EMU bond markets. For emerging markets, these findings are in agreement with Ahmad et al (2013).…”
Section: Determinants Of Net Spillovers Across Saarc Countriesmentioning
confidence: 91%
“…13 In the literature, some studies have used a different set of variables to explain the cross-country financial spillovers. Some of the significant studies are Dornbusch et al (2000), Csonto and Ivaschenko (2013), Piljak (2013), Gómez-Puig et al (2014), Fernández-Rodríguez et al (2015, 2016. In line with these studies, we consider following macroeconomic determinants viz., government debt as a percentage of GDP, current account balance-to-GDP, inflation and interest rates as measures of economic and policy competitiveness of SAARC nations.…”
Section: Determinants Of Net Spillovers Across Saarc Countriesmentioning
confidence: 99%